The Evolution of Grouting and Hydraulic Lime-Based Grout Used in the Restoration of Historical Masonry Buildings - Eksi Akbulut, Dilek; Gokyigit Arpaci, Enise Yasemin; Oktay, Didem; Yuzer, Nabi (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
In addition to serving as documentation of cultural existence historical structures are important part of the living environment. Thus, it is important to transfer them to future generations. Historical buildings that have been damaged over time due to various reasons are in need of conservation and restoration. However, methods applied with lack of scientific research can have harmful effects on the structure and create new damages. The scientific research on hydraulic, lime-based grout that is frequently used in the restoration of historical buildings is insufficient. In particular, the research on commercially sold lime-based grout needs more interest. The injection of grout is an irreversible technique and more scientific research can prevent unpredictable damages. Furthermore, although it is widely used, there are no national or international standards regarding the use of hydraulic lime-based grout. The aim of this study is to analyse the development of the grouting technique and the lime based grouts used in the restoration of buildings with historical masonry structure within the literature review context and to offer a contribution to the required standards and further scientific research. This research is an examination of the available resources in related topics in a chronologic order. First, the technique used to inject the grout during the restoration of buildings with historical masonry is described. Studies performed related to other grouts and mortars that contributed to the development of the use of hydraulic, lime-based grouts are discussed. Then, the development of the hydraulic, lime-based grout material and the test methods for this material are examined. There is also an analysis on the research performed with regard to the commercially available, hydraulic lime-based grouts. Finally, the previous and ongoing research considering the use of this grout in Turkey is mentioned in the scope of this study.
Keywords: Grouting; lime mortars; conservation; restoration; historical masonry buildings; WALLS; BEHAVIOR; DESIGN; Architecture